IMPLEMENTASI EKSTRAKURIKULER SANGGAR SASTRA AL-AMIEN (SSA) DALAM MENGEMBANGKAN BAKAT MENULIS SANTRIWATI DI TMI AL-AMIEN PRENDUAN - Fathorrahman, Fathorrahman; Zulfa, Ervina (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Writing is part of the aspects of language activities that are considered difficult and complained about by the community. Various levels of education complained about the difficulty of writing. The impact of these complaints gives the opinion that writing is indeed difficult. This opinion cannot be justified by his statement, because writing activities are the same as other language activities, which are skills. Every skill can be developed with systematic and continuous practice. Therefore educational institutions form extracurricular activity programs in developing students' writing talents to produce quality successors of the nation in writing activities. This study aims to find out how the extracurricular activities of the Al-Amien Literature Studio are implemented, and what are the implications and contributions of the extracurricular activities of the Al-Amien Literature Studio in developing the writing talents of female students at TMI Al-Amien Prenduan. This research is a descriptive qualitative using observation, interview, and documentation methods which are then analyzed to obtain data or information. The subjects of this study were taken Three persons from the trainers, two people from the charge, two persons from the consultants, and six members of the Al-Amien Literature Studio. For the validity of the data researchers triangulation. This thesis concludes that the implementation of the extracurricular activities of the Al-Amien Literature Studio is carried out through three stages, namely the planning, implementation, monitoring, and evaluation stages of the extracurricular activities. While the implications and contributions of the extracurricular activities of the Al-Amien Literature Studio are the use of active and creative methods, the existence of corrections or feedback activities on students' work, the efforts to improve the quality of writing, and the prevention and control of plagiarism on students' written works.